2008
DOI: 10.1007/s00228-008-0592-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of problem-based learning integration in a course on rational drug use: a comparative study between two Croatian medical schools

Abstract: The style of learning about medicines did not affect students' factual knowledge. Only half of the student cohort felt confident about their ability to prescribe medicines, and few had practiced this skill during their medical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
8
0
2
Order By: Relevance
“…Several investigations indicate that prescription training is effective in increasing the accuracy and rationality of prescribing practice 19–25 . In order to determine whether problem‐based teaching is also effective in reducing prescription errors in the clinical context, we examined the effects of a teaching module on prescribing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations indicate that prescription training is effective in increasing the accuracy and rationality of prescribing practice 19–25 . In order to determine whether problem‐based teaching is also effective in reducing prescription errors in the clinical context, we examined the effects of a teaching module on prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription is not only about selecting the best drug for a particular disease. There is some evidence to suggest that the rationality and accuracy of prescription can be enhanced by teaching modules 19–25 . In addition, Garbutt et al.…”
Section: Introductionmentioning
confidence: 99%
“…The problem based learning method was first used in medical faculties, thus most of the studies about problem based learning have been conducted in medical faculties (Drake & Long, 2009;Likic et al, 2009). Raupach et al (2010) indicated that using web supported, problem based learning, increases the academic achievements of medical students.…”
Section: Literature Review About Problem Based Learning and Concept Cmentioning
confidence: 99%
“…Studies indicate that 8–10% of prescriptions written by junior doctors contain errors, including fatal prescribing mistakes . Moreover, junior doctors report feeling unprepared for their prescribing responsibilities at the time of graduation .…”
Section: Introductionmentioning
confidence: 99%